Modeling and numerical simulations of shape memory alloys - Gao, Xiangyang (2008)
The aim of this project is to develop a simple 3-D Shape Memory alloy (SMA) model that can be easily adopted by commercially available finite element packages, for instance, ANSYS. A modified micro-mechanical model is developed to investigate the yield surfaces (transformation start stress) of SMAs.